Two-dimensional BiTeI as a novel perovskite additive for printable perovskite solar cells. Issue 23 (2nd November 2022) - Tsikritzis, Dimitris; Chatzimanolis, Konstantinos; Tzoganakis, Nikolaos; Bellani, Sebastiano; Zappia, Marilena Isabella; Bianca, Gabriele; Curreli, Nicola; Buha, Joka; Kriegel, Ilka; Antonatos, Nikolas; Sofer, Zdeněk; Krassas, Miron; et al.
Abstract : 2D BiTeI flakes were exfoliated and incorporated in PSCs as an additive in the perovskite layer. The energy level alignment changes from "cliff" to "spike" upon BiTeI incorporation. The FF increases to 82% and the PCE to 18.3%. Abstract : Hybrid organic–inorganic perovskite solar cells (PSCs) are attractive printable, flexible, and cost-effective optoelectronic devices constituting an alternative technology to conventional Si-based ones. The incorporation of low-dimensional materials, such as two-dimensional (2D) materials, into the PSC structure is a promising route for interfacial and bulk perovskite engineering, paving the way for improved power conversion efficiency (PCE) and long-term stability. In this work, we investigate the incorporation of 2D bismuth telluride iodide (BiTeI) flakes as additives in the perovskite active layer, demonstrating their role in tuning the interfacial energy-level alignment for optimum device performance. By varying the concentration of BiTeI flakes in the perovskite precursor solution between 0.008 mg mL −1 and 0.1 mg mL −1, a downward shift in the energy levels of the perovskite results in an optimal alignment of the energy levels of the materials across the cell structure, as supported by device simulations. Thus, the cell fill factor (FF) increases with additive concentration, reaching values greater than 82%, although the suppression of open circuit voltage ( V oc ) is reported beyond an additive concentration threshold of 0.03 mg mL −1 . The most performant devices delivered a PCE of 18.3%, with an average PCE showing a +8% increase compared to the reference devices. This work demonstrates the potential of 2D-material-based additives for the engineering of PSCs via energy level optimization at perovskite/charge transporting layer interfaces.